Unmasking the uncommon: a rare case of vulval leiomyoma mimicking a Bartholin cyst - Hasitha, Medarametla; Dhanalakshmi, M. G.; Meghana, Kanchibotla (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Vulval leiomyomas are rare benign smooth muscle tumors, often misdiagnosed due to their nonspecific presentation. They constitute approximately 3.8% of all benign soft tissue tumors in the vulvar region. We report the case of 30-year-old multiparous women, with a history of caesarean section five years’ prior, presenting with a three-month history of right-sided vulvar pain and swelling. Physical examination revealed a tender, cystic mass measuring 3×4 cm in the right labia, extending to the right lateral vaginal wall. A provisional diagnosis of a paraurethral mass was made. Surgical excision was performed under appropriate anesthesia. Histopathological examination confirmed the diagnosis of vulval leiomyoma. The patient’s postoperative course was uneventful, with no recurrence observed during follow-up. This case underscores the importance of considering vulvar leiomyoma in the differential diagnosis of vulvar masses. Accurate diagnosis relies on histopathological evaluation, and complete surgical excision remains the choice.